The Translation of Idiomatic Expressions in ‘The Adventures of Huckleberry Finn’ Novel from English into Indonesian - Hanim, Lutfia (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2022)
This research examines idiomatic expressions found in the translation of Twain’s ‘The Adventures of Huckleberry Finn’ from English into Indonesian; identifies the characteristics of idiomatic expressions; and investigates translator’s decision to apply the procedures of translating idiomatic expressions and equivalence. This research was data-driven study which focuses on idiomatic expressions found in an American novel, The Adventures of Huckleberry Finn written by Mark Twain (1884/2018) as the Source Text (ST) and its Indonesian translation by Ambhita Dhyaningrum (2011) as the Target Text (TT). The data was analyzed by using descriptive (qualitative)-comparative methods focusing on Kvetko’s (2009) characteristics of idioms, Catford’s (1965) formal correspondence and textual equivalence, and Newmark’s (1981) semantic and communicative translation. The findings show that demotivated/opaque idioms, partially motivated idioms/semi opaque, and semi idioms are identified in the idioms. In addition, verba, verbless, and minimal pair idioms are found. Moreover, the translator tends to apply translation shifts which depart from formal correspondence to achieve the textual equivalence. Nevertheless, sometimes the translation shifts occur without resulting in the textual equivalence. The translator also applies communicative translation which is more natural in the target language.